An analysis of CEE equity market integration and their volatility spillover effects - Ngo Thai Hung (European Journal of Management and Business Economics (EJM&BE), 2020)
Purpose The purpose of this paper is to examine the conditional correlations and spillovers of volatilities across CEE markets, namely, Hungary, Poland, the Czech Republic, Romania and Croatia, in the post-2007 financial crisis period. Design/methodology/approach The authors use five-dimensional GARCH-BEKK alongside with the CCC and DCC models. Findings The estimation results of the three models generally demonstrate that the correlations between these markets are particularly significant. Also, own-volatility spillovers are generally lower than cross-volatility spillovers for all markets. Practical implications These results recommend that investors should take caution when investing in the CEE equity markets as well as diversifying their portfolios so as to minimize risk. Originality/value Unlike the previous studies in this field, this paper is the first study using multivariate GARCH-BEKK alongside with CCC and DCC models. The study makes an outstanding contribution to the existing literature on spillover effects and conditional correlations in the CEE financial stock markets.
Keywords: 650; Volatility spillovers; DCC; BEKK; CCC; CEE finance; Conditional correlations